Running the United States-Mexican Border: 1909 through the Present - Gary D. Keller (Studies in 20th & 21st Century Literature, 2001)
A very large number of films have been and continue to be made about the border by both the United States and Mexican film industries. This is due primarily to the highly unusual nature of the United States-Mexico border itself, and because of various factors ranging from the Mexican Revolution of 1910, to the emergence of Westerns as the primary product of the United States film industry, and other economic, sociocultural, and technological reasons. This study is dedicated to an overview of the border films and strives to explain some of the major cultural, technological, historical, and economic factors that spurred them. It is broadly divided into three sections. The first establishes the conventions of the border in the popular mind, focusing attention on the role first of mass-produced dime novels, and subsequently of popular films. The second section reviews some of the most salient of those border conventions. The third shows how contemporary Chicano/Latino border films function to subvert and debunk those same conventions. Numerous films from American and Mexican studios and by independent Chicano producers made between 1909 through the present are cited and reviewed in historical context.
Keywords: U.S.-Mexico border; border narratives; film; Mexican Revolution; socioculture; economy; economics; border films; culture; mass-produced dime novels; chicano films; latino films